7(a+3)=6(a-6)

Simple and best practice solution for 7(a+3)=6(a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(a+3)=6(a-6) equation:


Simplifying
7(a + 3) = 6(a + -6)

Reorder the terms:
7(3 + a) = 6(a + -6)
(3 * 7 + a * 7) = 6(a + -6)
(21 + 7a) = 6(a + -6)

Reorder the terms:
21 + 7a = 6(-6 + a)
21 + 7a = (-6 * 6 + a * 6)
21 + 7a = (-36 + 6a)

Solving
21 + 7a = -36 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
21 + 7a + -6a = -36 + 6a + -6a

Combine like terms: 7a + -6a = 1a
21 + 1a = -36 + 6a + -6a

Combine like terms: 6a + -6a = 0
21 + 1a = -36 + 0
21 + 1a = -36

Add '-21' to each side of the equation.
21 + -21 + 1a = -36 + -21

Combine like terms: 21 + -21 = 0
0 + 1a = -36 + -21
1a = -36 + -21

Combine like terms: -36 + -21 = -57
1a = -57

Divide each side by '1'.
a = -57

Simplifying
a = -57

See similar equations:

| -3m+7=7 | | 6a+18-15+16-12a=0 | | -8x+13=-5(x-2) | | 6x-9x+9=x-4+13 | | 28-31/2 | | 6x+14-5x+1=51-18x | | 2(1+8x)=130 | | -5+m=27 | | -12+r=28 | | 7+5w=-28 | | 7(2m+3)= | | 5(3m-6)=150 | | 5(x-2)-4=-6(-3x+4)-9x | | 3m^2-19m-72=0 | | 4w+7=23 | | 10+2r=6-6(7r-8) | | -2+x/3=13 | | 7v+8=2v+3 | | 11=-v+268 | | (6-1)(2x+5)=168 | | (a-3)/5-(5(a-3))/8=(5a+25)/4 | | -(2k+8)-(3k-7)= | | (6-1)+(2x+5)=168 | | 275-y=50 | | 2c^2-5=3 | | .36X-.035Y=10 | | 6a-5+3a=4a-3 | | -4v/7=-24 | | 1/3x-1/4(x-2)=4x | | -9/5=3y | | .36X+.035Y=.10 | | 2(Z-38)=5(Z-59) |

Equations solver categories